Guess The Picture Animation App In An Effort To Increase The Effectiveness Of Discussion Students - Damai Yasa, I Wayan; Arsa Wiguna, I Made; Perbowosari, Heny (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
In line with the development of science, the technology also be a results that was born by the science. Then with technology also any kinds of knowledge can facilitate human in the absorb, received, obtained and develop science. So, between science and technology is two elements in the world of education that can help advances in his transformation knowledge to human. From the technology that simple, its slowly but surely until on sophisticated technology that so quickly can help the performance of human to produce the latest knowledge that have been able to created by human from the results of scientific development that he had. Therefore, technology is very also plays an important role in advancing the world of education. Including lately how humans have been able to find and create a variety of application technology in the form of ?Games? or some games that collaborated with educational activities and learning so as to foster a sense of human interest ranging among children until adults to learn a variety of things, while entertain himself.